A multinational, drug utilization study to investigate the use of dexmedetomidine (Dexdor®) in clinical practice in the EU. (10th May 2017) - Weatherall, Mary; Aantaa, Riku; Conti, Giorgio; Garratt, Chris; Pohjanjousi, Pasi; Lewis, Michael A.; Moore, Nicholas; Perez‐Gutthann, Susana
Abstract : Aims : Dexmedetomidine (dexdor®) is approved in the European Union (EU) for sedation of adults in the intensive care unit (ICU). The present observational, retrospective study was requested by the European Medicines Agency to investigate dexmedetomidine use in clinical practice, with a particular focus on off‐label use, including the paediatric population. Methods : Study countries and sites were chosen from those with highest dexmedetomidine use, based on sales. Site selection (blind) was conducted by a multispecialist, independent group. Anonymized data on demographics, treatment indication, dexmedetomidine dosing, concomitant medications and treatment effectiveness were collected retrospectively from records of all dexmedetomidine‐treated patients at the site during the enrolment period. Informed consent was waived, to avoid influencing the prescribing of dexmedetomidine. Recruitment was completed within 18 months of first site initiation. Results : Data from 2000 patients were collected from 16 hospitals in four EU countries (Finland 750, Poland 505, Germany 470, Austria 275). The median age was 62 years, with more males (70.2%) than females. Dexmedetomidine was primarily used in the adult ICU (86.0%) for ICU sedation (78.6%) and mostly dosed according the product label. The intended sedative effect was obtained in 84.9% of administrations. Paediatric use (5.9% of patients, mostly in Austria and Finland) occurred mainly in the adult or paediatric ICU (75.6%) for sedation (67.2%). Conclusions : Overall, most patients were treated with dexmedetomidine according to the product labelling. Use in children was limited but significant and similar in scope to that in adults. Administrations not fully according to the product labelling usually occurred in an ICU environment and reflected extensively investigated clinical uses of dexmedetomidine.